Transliterated Cuneiform Tablets of the Electronic Babylonian Library Platform - Yunus Cobanoglu; Jussi Laasonen; Fabian Simonjetz; Ilya Khait; Sophie Cohen; Zsombor Földi; Aino Hätinen; Adrian Heinrich; Tonio Mitto; Geraldina Rozzi; Luis Sáenz; Enrique Jiménez (Journal of Open Humanities Data)
This work presents a corpus of transliterated cuneiform tablets from the Electronic Babylonian Library (eBL) platform, including a public API endpoint to download the latest version of the data, and a Python library to parse the transliterations in ATF format. As of the time of writing, the constantly growing dataset contains around 25,000 tablets with over 350,000 lines of transliterated text. This dataset is a sizeable addition to open-source cuneiform data and a major milestone for research within the fields of cuneiform studies and NLP.